Genetic variants associated with physical performance and anthropometry in old age: a genome-wide association study in the ilSIRENTE cohort. Issue 1 (December 2017) - Heckerman, David; Traynor, Bryan; Picca, Anna; Calvani, Riccardo; Marzetti, Emanuele; Hernandez, Dena; Nalls, Michael; Arepali, Sampath; Ferrucci, Luigi; Landi, Francesco
Abstract Unraveling the complexity of aging is crucial for understanding its mechanisms and its role as a risk factor for most chronic conditions. Advancements marked by genome-wide association studies (GWASs) have sparked interest in gene cataloguing in the context of aging and age-related conditions. Here, we used GWAS to explore whether single nucleotide polymorphisms (SNPs) were associated with functional and anthropometric parameters in a cohort of old community-dwellers enrolled in theilSIRENTE study. Analyses were carried out in men and women aged 80+ years enrolled in theilSIRENTE study (n = 286) and replicated in theinCHIANTI study (n = 1055). Genotyping was accomplished on Infinium Human610-QUAD version 1. In theilSIRENTE population, genetic variants in ZNF295 and C2CD2 (rs928874 and rs1788355) on chromosome 21q22.3, were significantly associated with the 4-meter gait speed (rs928874, p = 5.61 × 10−8 ; rs1788355, p = 5.73 × 10−8 ). This association was not replicated in theinCHIANTI population. Our findings suggest that specific SNPs may be associated with a key measure of physical performance in older adults. GWASs using larger samples are needed to confirm these preliminary results to enhance our comprehension of complex age-associated phenomena.